P118 Defining a minimal clinically important difference in CAMPHOR. (12th November 2019) - Bunclark, K; Abraham, N; Ali, S; Cannon, JE; Sheares, K; Speed, N; Taboada, D; Toshner, M; Pepke-Zaba, J
Abstract : Background: The Cambridge Pulmonary Hypertension Outcome Review (CAMPHOR) questionnaire is an internally validated disease-specific patient-reported outcome (PROs) measure. Despite the widespread use of PROs as outcome measures in pulmonary hypertension clinical trials, changes in PRO scores which are deemed clinically relevant to the individual are unknown. We sought to identify the minimal clinically important difference (MCID) in the three CAMPHOR scales; Activities, Symptoms and Quality of Life in Idiopathic Pulmonary Arterial Hypertension (IPAH) using both distributional and anchor-based analyses. Method: Incident cases of IPAH between 2006 and 2018 with CAMPHOR scores available at treatment naïve baseline and one year post diagnosis were included. One-half of the standard deviation and one standard error of measurement were used in distributional analysis. Anchor-based methods used median CAMPHOR score change and receiver curve thresholds associated with a global health status change of 'moderately better'. Results: A total of 129 individuals were included (median age 55, SD 26 yrs). Median CAMPHOR scores at baseline were; Symptoms: 13 (SD 7), Activities: 11 (7) and Quality of Life 10 (7) and at one-year review; Symptoms: 10 (7), Activities: 11 (8) and Quality of Life: 8 (7). Distributional analyses yielded estimates of a MCID for Symptoms of 1.95–3.48, Activities: 2.75–3.67 and Quality of Life: 1.95 – 3.46. Anchor-based approaches yielded MCID estimates for Symptoms of -5.5 to -7.5, Activities: 4.5 to -5.5, and Quality of Life: -0.5 to -4.5. Using a triangulated approach MCIDs were derived for Symptoms: 5 points, Activities 4 points and Quality of Life 3 points. MCIDs predicted change in six-minute walk distance at one year (Activities adjusted p = 0.045; Symptoms p = 0.004). Conclusion: This is the first clinical investigation to estimate MCIDs in a pulmonary hypertension specific patient-reported outcome measure and provides a metric for understanding whether statistically significant changes in PRO end-points, are clinically relevant on an individual level.